Kinerja Bagian Organisasi Sekretariat Daerah Kota Bima Perspektif Otonomi Daerah - Salahuddin, Salahuddin; Permana, Djaka; Karnedi, Karnedi (Universitas Hamzanwadi, 2024)
This research aims to analyze the Organizational Performance of the Organizational Section of the Bima City Regional Secretariat from a Regional Autonomy Perspective. The research approach is qualitative research, and the key informants are the Bima City Regional Secretariat Organization Section officials. Data is analyzed using data reduction procedures, data presentation, drawing conclusions or verification. The results of research on the performance of the Bima City Regional Secretariat Organization section from the perspective of productivity, responsibility, accountability, efficiency and responsiveness are relatively good, shown by achieving high performance. This performance cannot be separated from leadership and organizational culture factors which influence the performance of the Bima City Regional Secretariat Organization Section.